Morphological Characteristics of the Posterior Wall Associated with Complex Acetabular Fractures: A Radiological Study Using 3D Software and Fracture Mapping Technique. (24th March 2022) - Tian, Siyu; Liang, Shaobo; Wang, Zhongzheng; Ye, Pengyu; Yin, Yingchao; Li, Junran; Zhang, Ruipeng; Zhao, Kuo; Hou, Zhiyong; Zhang, Yingze
Abstract : Background . The aim of the study was to compare the morphological distinctions of the posterior wall (PW) in different complex acetabular fractures using 3D software and fracture mapping technique and ultimately to provide for improved clinical treatment. Methods . One hundred and fourteen patients with complex acetabular fracture associated with PW were recruited. All patients were divided into two groups according to the injury mechanism of the PW: Group A (both-column and PW) and Group B (including posterior column and PW; T shape and PW; and transverse and PW). Fracture mapping was generated on the intra- and extrasurface of a standard template. The radiological parameters including spatial displacement, articular surface area, articular range, marginal impaction, and multifragments of the two groups were compared. Results . The spatial displacement, intra-/extra-articular surface area, and start and end point in Group A were 10.9 mm (IQR, 8.4-15.2), 8.2 ± 2.6 cm 2, 17.9 ± 5.3 cm 2, 0.8° (IQR, -6.0-16.2), and 107.5° (IQR, 97.2-116.9), respectively. The results in Group B were 30.4 mm (IQR, 16.8-48.7), 4.1 ± 2.0 cm 2, 10.6 ± 4.4 cm 2, 29.5° (IQR, 19.2-38.0), and 117.5° (IQR, 98.2-127.2), respectively. Marginal impaction was defined by Letournel et al. All the differences between two groups were significant (P < 0.05 ). The fracture map in Group A showed an "L"-shaped pattern and a "cusp" on the ilium, and the PW was located at 1/5 to 1/4 of the posterosuperior part of the acetabulum. The fracture maps in Group B were scattered and lacked consistency, and the PWs were confined to 1/10 to 1/8 of the posterior acetabulum. Conclusions . Quantitative measurements and fracture mapping represented the differences in morphological characteristics of PWs associated with complex acetabular fractures.